2019
DOI: 10.1097/jnr.0000000000000299
|View full text |Cite
|
Sign up to set email alerts
|

Frail Phenotype and Disability Prediction in Community-Dwelling Older People: A Systematic Review and Meta-Analysis of Prospective Cohort Studies

Abstract: Background: The World Health Organization has identified frailty as a crucial factor affecting successful aging. Systematic literature reviews have yet to focus on the relationship between stages of frailty and disability in community-dwelling older adults. Purpose: The purpose of this study was to investigate the relationships between various frailty types and disability in community-dwelling older adults and to explore how various frailty criteria have been used to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 25 publications
1
15
0
1
Order By: Relevance
“…Further, we found that the incident rate of disability illustrated significantly different trajectories of functional capacity between intra-city districts among the participants. Previous studies have observed regional differences in the prevalence of frailty and disability incidence among regions and countries [ 27 ] and in urban–rural areas among older people in China [ 28 ]. Generally, public health practitioners assess each indicator across districts by population groups or geographical areas and make policy choices to prioritize health inequalities within the city [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, we found that the incident rate of disability illustrated significantly different trajectories of functional capacity between intra-city districts among the participants. Previous studies have observed regional differences in the prevalence of frailty and disability incidence among regions and countries [ 27 ] and in urban–rural areas among older people in China [ 28 ]. Generally, public health practitioners assess each indicator across districts by population groups or geographical areas and make policy choices to prioritize health inequalities within the city [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notwithstanding, two main methods are extensively used to describe it: (i) the frailty phenotype, which is substantially based on the evaluation of residual physical strength [ 29 ]; (ii) the frailty index (FI), which is based on the concept that frailty is the result of the cumulative juxtaposition of various health deficits, provided that these are biologically determined [ 30 , 31 ]. Irrespective of its definition, frailty is associated with a significantly higher risk of death [ 32 , 33 ] and disability [ 34 ], as well as with higher healthcare costs [ 35 ].…”
Section: Definition Of Frailty and Impact On Atrial Fibrillationmentioning
confidence: 99%
“…The association between frailty and disability in ADL has been examined in multiple studies [ 31 , 32 , 33 ]. Three perspectives regarding the relationship between these concepts have been identified, with disability being (a) a negative health outcome of frailty, (b) a characteristic of frailty, and (c) a predictor of frailty [ 34 ].…”
Section: Introductionmentioning
confidence: 99%